2021
DOI: 10.1161/circresaha.120.316738
|View full text |Cite
|
Sign up to set email alerts
|

KLF5 Is Induced by FOXO1 and Causes Oxidative Stress and Diabetic Cardiomyopathy

Abstract: Rationale: Diabetic cardiomyopathy (DbCM) is a major complication in type-1 diabetes (T1D), accompanied by altered cardiac energetics, impaired mitochondrial function and oxidative stress. Previous studies indicate that T1D is associated with increased cardiac expression of Krüppel-like factor-5 (KLF5) and Peroxisome Proliferator Activated Receptor (PPAR)α that regulate cardiac lipid metabolism. Objective: In this study, we investigated the involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 84 publications
1
54
0
Order By: Relevance
“…In the cardiomyocytes, You et al found that KD contributes to the profibrotic actions in fibroblasts possibly via the mTOR signaling pathway in hypertension [6]. Besides, diabetes could modulate a wide range of cellular processes (e.g., autophagy, oxidative stress, and ferroptosis) in cardiomyocytes and endothelial cells, which could be important in the regulations of fibrosis during DCM development [45,46]. A lack of evidence on these aspects has restricted us to provide full information assessing the way that KD regulates DCM in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiomyocytes, You et al found that KD contributes to the profibrotic actions in fibroblasts possibly via the mTOR signaling pathway in hypertension [6]. Besides, diabetes could modulate a wide range of cellular processes (e.g., autophagy, oxidative stress, and ferroptosis) in cardiomyocytes and endothelial cells, which could be important in the regulations of fibrosis during DCM development [45,46]. A lack of evidence on these aspects has restricted us to provide full information assessing the way that KD regulates DCM in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…PPARα contributed to DiCM in this model by promoting triglyceride accumulation, resulting in a dysregulated oxidative stress status and mitochondrial dysfunction. Notably, Kyriazis et al recently reported PPARα-independent DiCM progression via molecular crosstalk between FOXO1 and KLF5 [148].…”
Section: Pparαmentioning
confidence: 99%
“…High glucose can cause oxidative stress and apoptosis of cardiomyocytes [6,29]. The utilization of glucose by 12 Oxidative Medicine and Cellular Longevity cardiomyocytes decreased in diabetes, which was conducive to the β-oxidation of free fatty acids (FFA).…”
Section: Discussionmentioning
confidence: 99%